Nitrile glucoside, flavonol glucoside and polyphenolic acids from Ehretia dentata Courch - Thuy, Trinh Thi; Cuong, Nguyen Huy; Sung, Tran Van (Vietnam Journal of Chemistry, 2014)
Chemical investigation of the leaves of Ehretia dentata Couch. growing in Hoa Binh, Vietnam led to the isolation and structural elucidation of a nitril glucoside, ehretioside A1, the flavonol glucoside astragalin, as well as rosmarinic acid and methyl rosmarinat. These structures were determined on the basis of MS and NMR spectroscopic data. Key words: Ehretia dentata; boraginaceae; nitrile glucoside; cyanoglucoside; astragalin; rosmarinic acid.